ANALISIS PENGARUH KECERDASAN EMOSIONAL PEMIMPIN, KEPUASAN, DAN LINGKUNGAN ORGANISASI TERHADAP LOYALITAS PENGURUS ORGANISASI MAHASISWA FAKULTAS EKONOMI UNIVERSITAS AHMAD DAHLAN - Fatoni Imam Wibowo; Utik Bidayati (Jurnal Fokus Manajemen Bisnis, 2016)
This study aims to determine the effect of emotional intelligence leaders, satisfaction, and organizational environment both partially and together towards the loyalty of the management of the Faculty Student Organization Economics of Ahmad Dahlan University Yogyakarta 2014/2015 period. This research is a quantitative research. Data collection with using a questionnaire method (questionnaire) that has been tested for validity and reliability, while data analysis is done using analysis multiple linear regression. The subjects of this research are all organizational management there are 153 students of the Faculty of Economics with engineering sampling using purposive sampling method, so the amount the sample used was 106 administrators. The results showed that: 1) Emotional intelligence of leaders no significant effect on the loyalty of the board. 2) Satisfaction no significant effect on the loyalty of the board. 3) Organizational environment positive and significant effect on the loyalty of the board shown from the results of the t test of 2.163 with a significance of 0.033. 4) Intelligence emotional leaders, satisfaction, and organizational environment together significant effect on the loyalty of the board, this is indicated from the results F test count of 12.273 with a significance of 0,000 and can be written with regression equation Y = -1,431 + 0,126ð‘‹1 + 0,181ð‘‹2 + 0,276ð‘‹ 3. With big influence of 26.5%, while the remaining 73.5% is influenced by other independent variables are not observed.